Preoperative Blood Glucose Level Predicts Postsurgical Gastroparesis Syndrome after Subtotal Gastrectomy: Development of an Individualized Usable Nomogram - Chenchen Mao; Xin Liu; Yunshi Huang; Mingming Shi; Weiyang Meng; Libin Xu; Weisheng Chen; Yuanbo Hu; Xinxin Yang; Xiaodong Chen; Xian Shen (Journal of Diabetes Research)
Background. Postsurgical gastroparesis syndrome (PGS) after subtotal gastrectomy imposes significant social and economic burdens. We aimed to investigate the relationship between preoperative blood glucose level and PGS and develop a nomogram for individualized prediction. Patients and Methods. We retrospectively analyzed 633 patients with gastric cancer who underwent subtotal gastrectomy. Preoperative blood glucose levels were evaluated via receiver operating characteristic (ROC) curve analysis. Chi-squared tests and multivariable logistic regression analyses were used to develop a predictive model for PGS, presented as a nomogram, which was assessed for its clinical usefulness. Results. Thirty-eight of 633 patients were diagnosed with PGS. Based on the ROC curve analysis, the preoperative blood glucose cutoff value for PGS was 6.25 mmol/L. The predictors of PGS included preoperative hyperglycemia (odds ratio (OR) 2.3, P=0.03), body mass index (BMI; OR 0.21, P=0.14 for BMI<18.5 and OR 3.0, P=0.004 for BMI>24), and the anastomotic method (OR 7.3, P=0.001 for Billroth II and OR 5.9, P=0.15 for Roux-en-Y). The predictive model showed good discrimination ability, with a C-index of 0.710, and was clinically useful. Conclusions. Preoperative hyperglycemia effectively predicts PGS. We present a nomogram incorporating the preoperative blood glucose level, BMI, anastomotic method, and tumor size, for individualized prediction of PGS.